Tailoring Carbon Materials Substrate to Modify the Electronic Structure of Platinum for Boosting Its Electrocatalytic Activity. Issue 5 (14th March 2018) - He, Jinling; He, Xiaofeng; Liu, LiangLiang; Hu, Binbin; Bai, Feng; Zhang, Peng; Zhao, Yong
Abstract : Tailoring chemical architecture of precious-metal based materials provides the opportunity to improve their catalytic activity, which is important for various kinds of fuel cells. Herein, we show that iron/cobalt/nitrogen codoped carbon (FeCo/C/N) substrate can greatly promote electrocatalytic oxygen reduction reaction (ORR) activity of platinum by modifying its' electronic structure in comparison to those of nitrogen/carbon and carbon supports. FeCo/C/N substrate induces the negative shift of Pt 4f binding energy and increases the electron density of Pt outer orbital, which is used for the optimization of absorption energy between ORR intermediates and Pt surface. The experiments and theoretical simulation confirm the change of Pt electronic structure and enhancement of ORR kinetic, which provide a guiding principle for rational design of Pt-based ORR catalysts.